2020
DOI: 10.1101/2020.07.07.191189
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FIP200 organizes the autophagy machinery at p62-ubiquitin condensates beyond activation of the ULK1 kinase

Abstract: AbstractMacroautophagy is a conserved degradation pathway, which mediates cellular homeostasis by the delivery of harmful substances into lysosomes. This is achieved by the sequestration of these substances referred to as cargo within double membrane vesicles, the autophagosomes, which form de novo. Among the many cargoes that are targeted by autophagy are condensates containing p62 and ubiquitinated proteins. p62 recruits the FIP200 protein to initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…We found, however, that the KD version of the ULK1 complex was as effective in promoting LC3 lipidation as wild type. This result is consistent with recent studies that found ULK1 kinase activity to be dispensable for PI3KC3-C1 activation induced by starvation (60) and autophagosome formation at p62 condensates (61).…”
Section: Discussionsupporting
confidence: 93%
“…We found, however, that the KD version of the ULK1 complex was as effective in promoting LC3 lipidation as wild type. This result is consistent with recent studies that found ULK1 kinase activity to be dispensable for PI3KC3-C1 activation induced by starvation (60) and autophagosome formation at p62 condensates (61).…”
Section: Discussionsupporting
confidence: 93%
“…FIP200 recruitment results in the local generation of phosphatidylinositol 3-phosphate, which in turn induces recruitment of WIPI2. 37 , 62 Therefore, we assayed whether p62 is required for Halo-WIPI2b puncta formation following 2 h of 750 μM LLOMe. We observed that p62 knockdown resulted in significantly fewer WIPI2b puncta as compared with control siRNA ( Figures 4F and 4G ), whereas co-expression of siRNA-resistant WT p62 construct rescued formation of WIPI2b puncta to control levels.…”
Section: Resultsmentioning
confidence: 99%
“…And the N-terminal domain (NTD) of the FIP200 forms a C-type scaffold, providing a hub for the assembly of the ULK1 complex ( Shi et al, 2020b ). Besides, FIP200 organizes autophagic mechanisms at p62-ubiquitin condensates beyond to ULK1 kinase activation ( Turco et al, 2020 ). And FIP200 coiled-coil and autophagic adapter NDP52 allosterically activate ULK1 complex membrane recruitment ( Shi et al, 2020a ).…”
Section: Atg1/ulk1 Complex Formation and Structurementioning
confidence: 99%